2006
DOI: 10.1080/09513590601012587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leptin on the regulation of placental hormone secretion in cultured human placental cells

Abstract: Placenta is an important source of leptin during pregnancy that contributes to the high plasma leptin levels in pregnant women. Leptin and its functional receptors are synthesized in trophoblast cells that, in turn, secrete gestational hormones supporting a paracrine or autocrine role for leptin in the endocrine activity of the placenta. In the present study we examined the effect of leptin on in vitro release of gestational hormones (human chorionic gonadotropin (hCG), human placental lactogen (hPL), progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Thus, it seems unlikely that action on the prolactin-responsive neurons is directly causing the reduction in pSTAT5 after leptin treatment during pregnancy. It is also unlikely that leptin treatment directly leads to a decrease in placental lactogen concentrations as in vitro studies have shown that leptin has no effect on the secretion of placental lactogen from the placenta (Coya et al 2006, Fuglsang et al 2008. Both leptin and prolactin are thought to enter the brain by active, saturable transport mechanisms, and it is tempting to speculate about possible competition between leptin and prolactin for entry into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems unlikely that action on the prolactin-responsive neurons is directly causing the reduction in pSTAT5 after leptin treatment during pregnancy. It is also unlikely that leptin treatment directly leads to a decrease in placental lactogen concentrations as in vitro studies have shown that leptin has no effect on the secretion of placental lactogen from the placenta (Coya et al 2006, Fuglsang et al 2008. Both leptin and prolactin are thought to enter the brain by active, saturable transport mechanisms, and it is tempting to speculate about possible competition between leptin and prolactin for entry into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Most signi cantly, the regulation of proin ammatory cytokines produced in the intrauterine environment, may suggest roles for leptin in regulating endometrial attachment (Schulz et al, 2009), modulating myometrial contractility, cervical ripening, and the rupture of conceptus membranes (Lappas et al, 2005), all of which signi cantly impact the processes associated with parturition. Coya et al (2006) reported that leptin led to a dosage-dependent decline in estradiol release by human term placental cells in culture. Indeed, leptin may be important for placental maintenance itself, as leptin introduced into choriocarcinoma cell cultures (a model for trophoblastic development) proved to be a signi cant trophic and mitogenic factor by inhibiting apoptosis and promoting cell proliferation in a dosage-and time dependent manner (Magarinos et al, 2007).…”
Section: Mechanisms Of Cadmium-related Placental Effectsmentioning
confidence: 98%
“…In trophoblasts cells, the synthesis and secretion of leptin as well as its functional receptors were widely demonstrated (Masuzaki et al 1997, Senaris et al 1997, suggesting that leptin may act as a modulator of placental endocrine function (Coya et al 2006). In this way, it was reported that leptin increases the matrix metalloproteinase expression in cytotrophoblasts, facilitating the implantation process (Castellucci et al 2000).…”
Section: Introductionmentioning
confidence: 99%